Effectiveness of Evaluation Evidence to Influence Change in Primary Education Sub-sector in Uganda - Wokadala, James (Advances in Social Sciences Research Journal, 2020)
A well-designed impact evaluation study in the education sector is relevant in informing decision and policymaking based on high-quality evidence generated from the research. In this paper, we provide a chronology on how we developed and implemented an impact evaluation on school facilities grant (SFG) programme designed to support Government aided primary schools in Uganda – to construct classrooms, sanitation facilities as well as teacher houses. We describe the appropriate methodology, randomization designs implemented and the target groups. Results revealed that selecting a clear intervention with identified observable and unobservable characteristics is important for the robust results. Measuring attribution on outcomes may also require a balance on internal and external validity checks and analysis. The internal validity, in addition to statistical measures also requires stakeholders’ engagement in the impact study process as a way of promoting social audits of public programmes. Finally, a well-planned and designed evaluation often leads to increased public trust in the findings and evidence uptake hence informing policy decision in management of programmes and projects.